KEMANFAATAN PEMBIAYAAN INFRASTRUKTUR NON KONVENSIONAL SEBAGAI ALTERNATIF PEMBIAYAAN INFRASTRUKTUR GUNA KETAHANAN EKONOMI NASIONAL - Karsayuda, M. Rifqinizamy; Fadli, Moh; Khusaini, Moh; Kusumaningrum, Adi (KLAUSULA (Jurnal Hukum Tata Negara Adminitrasi Dan Pidana), 2023)
Infrastructure is an instrument to facilitate the rotation of the economy so that it can accelerate development. Funding is a major challenge in national infrastructure development. The state budget is only able to support about one-third of the total infrastructure funding required. Unconventional financing alternatives provide significant benefits to national infrastructure development. Unconventional state-owned infrastructure financing has a positive impact on national economic resilience. Increasing the speed of infrastructure development by using non-conventional approaches, infrastructure development can be accelerated because it can involve private participation in financing and managing infrastructure projects. This research uses normative juridical method by using statutory approach and conceptual approach.